A qualitative study of mothers’ feeding practices for stunted toddlers in coastal areas - Rahmatuz Zulfia; Hasriana Hasriana (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Stunting is a chronic malnutrition condition that reflects the cumulative effects of inadequate nutritional intake over time. Feeding practices are among the modifiable factors associated with stunting. Although coastal areas have abundant potential sources of marine animal protein, the prevalence of stunting remains a persistent public health problem. Purpose: To explore mothers’ experiences in feeding practices among toddlers with stunting in coastal areas. Method: A qualitative design with a descriptive phenomenological approach. The participants were 17 mothers of stunted toddlers living in the coastal area of Tarakan City. Data were collected through semi-structured in-depth interviews and direct observation, and were analyzed using thematic analysis. Data trustworthiness was ensured through source triangulation and member checking with participants. Results: Four main themes emerged from the analysis: (1) the coastal food ecosystem: between marine potential and structural constraints; (2) dietary transition: the dominance of instant foods and snacking culture; (3) maternal dilemma: psychological burden and resilience in feeding practices; and (4) socio-cultural influences and support systems in feeding practices. Conclusion: Feeding practices among stunted toddlers are influenced by economic constraints, food access, and maternal capacity. Community-based interventions should strengthen maternal support and practical nutrition education.